The Implementation of Cultural and Religious Empowerment for Social Cohesion: A Local Governance Perspective - Susilo, Rachmad Kristiono Dwi; Syahputra, Muhammad Yusril Indra (Journal of Governance and Public Policy, 2026)
This research focuses on the implementation of community empowerment grounded in cultural and religious values to strengthen social cohesion from a local governance perspective, using a case study of the religious brotherhood program in Magelang City, Central Java, Indonesia. Using a case study-based qualitative method, this research collected data through in-depth interviews, observations, document studies, and focus group discussions. The concept of local governance developed in public policy studies was used. The findings indicated that religious and cultural empowerment has followed governance principles such as decentralization and multi-actor relations. As a process, the implementation of this policy has created three models of empowerment: empowerment through the formalization of religious and cultural practices, empowerment through new religious and cultural creations, and no empowerment. However, local governance still faces effectiveness challenges, including a lack of connectivity among actors and limited community participation. The next problem is that there is no shared understanding of the concept among the field's actors. This finding highlights the close relationship between community empowerment and governance: strengthening governance mechanisms enhances the effectiveness of community empowerment programs grounded in cultural and religious values. This finding fills a gap in previous studies on empowerment that were separate from governance. The study contributes, theoretically, to understanding local governance effectiveness in promoting empowerment and social cohesion, and, practically, to improving empowerment initiatives in religious and cultural domains.